Investigating the feasibility of ammonia as a decarbonised energy vector for marine applications - Ambalakatte, Ajith (2023)
The thesis details work conducted to analyse the feasibility of ammonia as a decarbonised energy vector for applications in the marine sector. Ammonia is now gathering significant interest due to being a zero carbon energy vector potentially produced from water, air and renewable energy. To understand the viability of ammonia, a review of competing energy vectors such as hydrogen and methanol was conducted with the relative strengths and weakness assessed. The key challenges with ammonia were deemed to be with its safety and could be overcome by proper education and control of fuel handling. Following this, extensive reviews were carried out on the various production, storage and energy conversion technologies that enable the use of ammonia as energy vector. The review of the application of ammonia in internal combustion engines revealed a lack of prior scientific work related to the use of high energy combustion systems (plasma/radical initiated) in Internal combustion (IC) engines for improving combustion of ammonia. Pre-chamber Jet ignition (JI) is one such solution where a small amount of fuel is combusted in a pre-chamber producing a jet of reactive products that are distributed in the main-chamber and initiate the combustion at multiple sites in the main-chamber. The distributed ignition of JI enables it to achieve fast burn rates with shorter flame travel and short burn duration. Since ammonia suffers low laminar flame speed, there was a synergy to use JI to overcome this challenge. As a result, this became the primary focus of this work, particularly in the backdrop of several marine engine manufacturers recently proposing the use of ammonia in large MW scale engines without sufficient evidence of feasibility in the public domain. To evaluate the viability of JI as potential combustion system for ammonia powered IC engines, a single cylinder gasoline direct injection engine was upgraded to incorporate a port fuel ammonia injection system. With the engine capable of operating in spark ignition (SI), passive and active jet ignition, tests were initially conducted with spark ignition system to act as benchmark for the tests with JI systems. However, initial commissioning tests conducted with the aim of understanding the maximum viable substitution of ammonia in the engine and identifying the limitations of the test cell revealed several challenges that needed to be resolved before benchmarking tests could be carried out. While the hardware could operate on pure ammonia for engine speeds between 1000 and 1800rpm at a load of 12bar IMEPn (Net Indicated Mean Effective Pressure), increasing the speed or reducing the load degraded the combustion, requiring increase in the amount of gasoline (pump grade E10) co-fuelling to avoid misfires. Furthermore, higher load tests were limited by the ammonia flow rate the supply line could deliver. To help overcome these challenges, the geometric compression ratio of the engine was upgraded from 11.33 to 12.39 via a piston swap along with new camshafts which improved the effective compression ratio from 10.3 to 12.02 for the same valve overlap conditions. With these upgrades it was possible to operate the engine in pure ammonia at lower loads in a fully warmed up state. A test region was mapped with this iii | P a g e configuration to act as benchmark for the jet ignition tests, the results show that pure ammonia operation prefers low speed operation achieving 100% substitution at loads as low as 6bar IMEPn which increases to 9bar IMEPn at 1800rpm. When it comes to efficiency and emissions, pure ammonia operation achieved similar or slightly higher efficiencies by virtue of its favourable anti-knocking characteristics, while all carbon emissions and NOx decreased considerably compared to pure E10 operation. The tests conducted with the passive jet ignition systems were less favourable, with the engine unable to operate on pure ammonia in any of the test points selected for benchmarking. The results show the increase in flame development phase of the combustion which along with the inability to advance the spark results in poor substitution for ammonia. However, for similar substitutions, jet ignition systems offer better efficiency and emissions, indicating the potential of the systems provided the challenges with combustion inside the pre-chamber can be overcome (associated with non-optimised geometry for the ammonia fuel possessing relatively high quench distance and a critical topic for future work).